Publishing the North: Bias, Diversity and the North–South Divide in the UK Book Industry - Bowden, Jen (Publishing Research Quarterly, 2025)
This article explores the place of writers and writing from Northern England in the contemporary UK book industry by highlighting the biases faced by these writers and the subsequent challenges of underrepresentation and cultural stereotyping that they experience in that industry. Through analysis of research conducted by interviews with UK book industry professionals such as publishers, writers and literary organisations, this paper argues that there is a clear social, cultural, geographic and political North–South divide in the UK generally and in the UK book industry specifically. Furthermore, it shows how this divide links to issues of class and influences the publishing industry’s response not just to Northern dialects, settings or characters in fiction but also to the authors themselves. This article also touches upon the need for greater representation of diversity in both the UK book industry and the literature published in the UK in order to authentically represent the diverse population of the UK in contemporary fiction.